The Digital Behaviour of Adult Consumers Aged 45–65 - Myhre, Christopher James (Auckland University of Technology, 2022)
The aim of this report is to synthesise literature regarding the digital behaviours of consumers aged between 45 – 65 years old as research regarding this topic is lacking compared to other age group and its importance is underrepresented. The global population is demographically changing with the over 65 age group is growing faster than any other, and their digital consumption is keeping pace with this growth. Research on technology has traditionally been targeted either towards the ‘younger generations’ or comparing the young and the old. So where does that leave the consumer in between? The research methodology employed in this report is a systematic literature review which enabled a thematic view of the current information on digital consumer behaviour. This was achieved through a synthesis of research resulting in 51 peer-reviewed articles selected for analysis and discussion. The research objectives were to extract salient themes from the current literature, filter and select poignant articles for critical analysis, and compile potential directions for future research. The results of the literature synthesis indicate the research regarding 45 to 65-year-old digital consumers is fragmented in the conclusions and approaches. The findings show a disparity between the terms used to describe older consumers resulting in difficulties with study comparisons. Further, there are potential biases from persistent assumptions about the aging process that filter down to the middle-aged digital user seemingly affecting the validity of the research. This review contributes a holistic summary of the literature on digital behaviour for the middle-aged consumer by identifying knowledge gaps and presenting opportunities for further investigation. The research findings highlighted key themes such as, but not limited to, an over reliance on using age as a behavioural predictor variable, the reporting of adoption rates for describing a sample population’s digital use, a lack of post-adoption analysis for the 45 to 65 age group, and a dearth of research where context was factored into the conclusions drawn about digital use. Of note, the pandemic-inspired lockdowns have potentially altered digital behaviour for all ages and, with the working population forced to adapt to new digital solutions, the middle-aged digital user is arguably the most affected cohort. With the findings of this report in mind, the significance of this research is that it provides opportunities for future research by finding ‘where we are' to enable the academic fraternity to find ‘where to go’.